2020
DOI: 10.1371/journal.pone.0232773
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and re-treatment results of HCV patients in the DAA era

Abstract: Background Re-treatment in patients with a chronic hepatitis C virus (HCV) infection and a previous failure to direct-acting antiviral (DAA) treatment remains a challenge. Therefore, we investigated the success rate of treatment and re-treatment regimens used at our center from October 2011 to March 2018. Methods A retrospective analysis of DAA-based HCV therapies of 1096 patients was conducted. Factors associated with a virological relapse were identified by univariable and multivariable logistic regression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
4
5
0
1
Order By: Relevance
“…In this regard, similar results were reported by the few relevant real world studies (85% Dietz et al [7] & Piecha et al [15]. and 86% by Zarębska-Michaluk et al [3].…”
Section: Svr12n=22supporting
confidence: 88%
See 1 more Smart Citation
“…In this regard, similar results were reported by the few relevant real world studies (85% Dietz et al [7] & Piecha et al [15]. and 86% by Zarębska-Michaluk et al [3].…”
Section: Svr12n=22supporting
confidence: 88%
“…It is noteworthy to mention that, lack of RAS testing before initiation of retreatment did not seem to affect retreatment results in this study (88% SVR rate), an observation that has also been reported by other real-world studies [15].…”
Section: Svr12n=22supporting
confidence: 85%
“…Similar to our findings, several studies showed that the SOF/DCV regimen is effective for the treatment of CHC. Babatin et al reported SVR 100% in all studied GT4 patients treated for 12 weeks with either SOF/SIM ± RBV (group 1) or SOF/DCV ± RBV (group 2) [34]. Another study showed a SVR12 rate of 96.67% in treating non-cirrhotic GT4 patients with SOF/DCV [35].…”
Section: Discussionmentioning
confidence: 98%
“…Este resultado señala la necesidad de realizar estudios para caracterizar los factores de riesgo de estos pacientes y documentar la introducción de este genotipo prevalente en Egipto. Además, la genotipificación es indispensable en casos de VHC con factores de riesgo, dada la posibilidad de reinfección luego del tratamiento con AAD ( 68 , 69 ).…”
Section: Discussionunclassified